Middle to Late Pleistocene lake-level fluctuations of Lake El'gygytgyn, far-east Russian Arctic - Fedorov, Grigory; Andreev, Andrei A.; Raschke, Elena; Wennrich, Volker; Schwamborn, Georg; Glushkova, Olga Y.; Juschus, Olaf; Zander, Anja; Melles, Martin (WILEY, 2019)
Lake El'gygytgyn, located in central Chukotka, Russian Arctic, was the subject of an international drilling project that resulted in the recovery of the longest continuous palaeoclimatic and palaeoenvironmental record for the terrestrial Arctic covering the last 3.6 million years. Here, we present the reconstruction of the lake-level fluctuations of Lake El'gygytgyn since Marine Isotope Stage (MIS) 7 based on lithological and palynological as well as chronological studies of shallow-water sediment cores and subaerial lake terraces. Reconstructed lake levels show an abrupt rise during glacial-interglacial terminations (MIS 6/5 and MIS 2/1) and during the MIS 4/3 stadial-interstadial transition. The most prominent lowstands occurred during glacial periods associated with a permanent lake-ice cover (namely MIS 6, MIS 4 and MIS 2). Major triggering mechanisms of the lake-level fluctuations at Lake El'gygytgyn are predominantly changes in air temperature and precipitation. Regional summer temperatures control the volume of meltwater supply as well as the duration of the lake-ice cover (permanent or seasonal). The duration of the lake-ice cover, in turn, enables or hampers near-shore sediment transport, thus leading to long-term lake-level oscillations on glacial-interglacial time scales by blocking or opening the lake outflow, respectively. During periods of seasonal ice cover the lake level was additionally influenced by changes in precipitation. The discovered mechanism of climatologically driven level fluctuations of Lake El'gygytgyn are probably valid for large hydrologically open lakes in the Arctic in general, thus helping to understand arctic palaeohydrology and providing missing information for climate modelling.